What is behind the weakness in global investment? - Maxime Leboeuf; Bob Fay (Bank of Canada, 2016)
The recovery in private business investment globally remains extremely weak more than seven years after the financial crisis. This paper contributes to the ongoing policy debate on the factors behind this weakness by analyzing the role of growth prospects and uncertainty in explaining developments in non-residential private business investment in large advanced economies since the crisis. Augmenting the traditional models of investment with measures of growth expectations for output and uncertainty about global demand improves considerably the ability to explain investment growth. Our results suggest that the main driver behind the weakness in global investment in recent years is primarily a pessimistic outlook on the part of firms regarding the strength of future demand. Lower levels of uncertainty have supported investment growth modestly over 2013-14. Similarly, diminishing credit constraints, lower borrowing costs and relatively stronger corporate profits have also supported the recovery in business investment from 2010 onward. Our findings have two important implications for the global outlook for investment. First, the expected improvements in global growth should support a recovery in investment; however, a slowdown in growth in emerging-market economies or further growth disappointment in advanced economies could restrain this recovery. Second, the ongoing recovery in investment remains vulnerable to uncertainty shocks.
Keywords: C23; C33; D24; E22; D80; D84; F01; G31; 330; Business fluctuations and cycles; Central bank research; Domestic demand and components; Economic models; International topics; Recent economic and financial developments; Uncertainty and monetary policy